Detention and Torture in Guantanamo - Maran, Rita (Social justice, 2006)
Part of a special issue on deaths in custody and detention. The writer presents an overview of the U.S. military camp at Guantanamo Bay, Cuba, and of issues that have entered the public discourse because of it, in the over five years since detention commenced in January 2002. She discusses torture at Guantanamo from the perspective of international human rights law. Specifically, she examines several outstanding areas of concern that have emerged because of Guantanamo, including its legal status, the issues of human rights law raised in connection with torture, how such matters have been addressed in the context of the UN system, and some notable U.S. government executive and judicial actions in relation to rule of law.